2015
DOI: 10.3391/ai.2015.10.4.09
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the invasive round goby, Neogobius melanostomus (Pallas, 1814), based on laboratory size preference and field diet in different habitats in the western basin of Lake Erie

Abstract: Taking into account the continuous increase in freshwater introductions, and to support the recent European legislation on invasive alien species, the identification of priority pathways and gateways of introductions is of utmost importance to develop adequate control strategies. The aim of this paper was to analyse the main pathways and gateways of introductions of freshwater alien species in Europe. Based on a thorough review of the scientific and grey literature, information on pathways, country and year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Gobies were able to swallow all small and medium crayfish, but also to kill and partially consume the larger prey as larger crayfish were rather too big for smaller goby individuals. Non-selectivity of round goby was confirmed with mussels as prey (Perello et al, 2015). Ray and Corkum (1997) observed that round gobies spit out the entire mussel shell as well as pieces, similar to our observations of crayfish cuticula in aquaria.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Gobies were able to swallow all small and medium crayfish, but also to kill and partially consume the larger prey as larger crayfish were rather too big for smaller goby individuals. Non-selectivity of round goby was confirmed with mussels as prey (Perello et al, 2015). Ray and Corkum (1997) observed that round gobies spit out the entire mussel shell as well as pieces, similar to our observations of crayfish cuticula in aquaria.…”
Section: Discussionsupporting
confidence: 86%
“…Round goby usually preys upon small bottom-dwelling vertebrates and invertebrates (Mikl et al, 2017), but is adaptable to feeding on a wide array of available prey types, including scavenging of carcasses, and particle sizes (Polačik et al, 2009(Polačik et al, , 2015Perello et al, 2015). Crustaceans and mollusks represent the most important food items (Brandner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another way in which temperature governs the performance of a species is through its effects on feeding behaviour (e.g., Iacarella et al 2015;Perello et al 2015). Maximum feeding rates of round goby in this study were highest at temperatures ≤24°C.…”
Section: Feeding Behaviour and Body Conditionmentioning
confidence: 60%
“…This study presents evidence of a similar behavior pattern in a native (European bullhead) and an invasive (round goby) benthic fish species in single-species laboratory experiments. The Ponto-Caspian invader, the round goby, continues to spread in European and North American freshwater and coastal ecosystems and invades vulnerable tributaries of main waterways where it threatens native fish species, competing with them for habitat and prey [ 3 , 36 , 42 ]. Examples of vulnerable native fish species negatively affected by the round goby are the log-perch Percina caprodes (Rafinesque 1818) [ 43 , 44 ] and the mottled sculpin Cottus bairdii (Girard 1850) [ 4 , 36 ].…”
Section: Discussionmentioning
confidence: 99%